(untitled) (Journal of Pathology of Nepal, 2022)
Background: Among the parameters that have a prognostic and/or predictive significance to therapeutic response, in the case of breast carcinoma, the study of tumor-infiltrating lymphocytes in breast carcinomas is emerging. The present study aimed to access the clinicopathological profiles of tumor-infiltrating lymphocytes in patients with primary breast carcinoma. Materials and Methods: Information was collected from the archive of the Department of Pathology, about invasive breast cancers diagnosed between April 2019 –March 2020. Hormone receptor status and Ki-67 index were assessed. For tumor-infiltrating lymphocytes, hematoxylin and eosin sections were evaluated following the guidelines of the “International Working Group for tumor-infiltrating lymphocytes in Breast Cancer—2014”. Results: High tumor-infiltrating lymphocytes were seen in 64.2% and 43.8% in ages < 50 and > 50 respectively. All cases of invasive lobular carcinoma had low tumor-infiltrating lymphocytes. 62.5% of T1 tumors were associated with low TILs whereas 80% of low tumor-infiltrating lymphocytes were T3. 71.4% of lymph node-positive tumors had low tumor-infiltrating lymphocytes. All breast cancers showed lymphocytic infiltrate. 40% of the tumors showed intermediate to high tumor-infiltrating lymphocytes. Lymphocyte-predominant breast cancers were 30%. Among the LPBC, 55.5% were triple-negative breast cancers, 33.3% were HR+, and 11.2% were HER2 positive. Conclusions: Low tumor-infiltrating lymphocytes presented at an advanced stage of the disease at the time of diagnosis. tumor-infiltrating lymphocytes in breasts decreased with increasing age. LPBCs were predominantly TNBCs. All breast cancers were immunogenic, stating the necessity to report tumor-infiltrating lymphocytes in all breast carcinomas.